Analisis Reaksi Pasar Dan Kinerja Perusahaan Terhadap Employee Stock Option Program (Studi Pada Publik Company Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Nindi Aulia Riadi; Ronny Malavia Mardani; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to analyze the market reaction and company performance to the employee stock option program. This research is quantitative research with secondary data collection techniques. In this study numbered 12 companies in a five-year period. Sampling techniques used are purposive sampling method. Secondary data processing using multiple regression analysis. The results of this study indicate that simultaneously market reaction and company performance have a positive and significant effect. Partially, the market reaction has a positive and significant effect on the employee stock option program, while the company's performance has no effect on the employee stock option program. Keyword: Market Reaction, Company Performance, Employee Stock Option Program.